REINVENTING ARTISTIC IDENTITY IN THE AGE OF ALGORITHMS - Amin, Rahul; Srivastava, Swati; Singh, Manpreet; Bhushan, Bharat; Poudwal, Jairam; Pandey, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The concept of artificial intelligence is transforming the principles of artistic practice by breaking the old assumptions about the creative process, authorship, and aesthetic value. The paper discusses the phenomenon of emerging hybrid artistic identity in the era of algorithms by providing a comprehensive study of history and evolution, theory, sociocultural processes, and ethical and legal imperatives. It considers that the art identity is no longer a unique, man-made machinery but a distributed mechanism in which the creative agency is a collaboration of human intention and computational processes of generative algorithms. The paper develops the most important theoretical ideas, such as distributed intention, algorithmic aesthetics, posthuman creativity, and procedural meaning-making to provide the understanding of how AI-based artworks are dissimilar to the traditional human-based models of expression. Empirical comparisons over visual features and emotional value show the presence of distinctive aesthetic differences between human and machine output which highlight the appearance of computationally native forms that are influenced by the latent-space representation and not based on subjective experience. The paper also examines the key sociocultural effects of AI art, including the democratization of access to creativity, oversaturation of the market, the change in the understanding of authenticity, and the transformation of art education. The essential ethical and legal issues such as provenance of datasets, authorial responsibility, cultural bias, and unclear copyright status of AI-generated are discussed in order to highlight the necessity of clear regulatory frameworks and culturally diverse datasets. Multimodal AI systems, self-evolving generative models, and collaborative human-AI creative platforms are some of the future directions being pursued, which will continue to influence the production, curation, and experiences of art. The research paper comes to the conclusion that AI is not something that is going to displace human creativity but rather a transformational companion that broadens the conceptual and expressive limits of art. The age of algorithms is eventually heralding a new paradigm of fluid artistic identity, based on relations and technologically co-constructed.